316 High grade transformation of low-grade endometrial stromal sarcoma; a morphological, immunohistochemical and molecular case study. (13th November 2020) - Ralte, A; Showeil, R; Sproston, A; Wilkinson, N
Abstract : Objective: Endometrial stromal tumours are rare uterine mesenchymal neoplasms whose classification has changed over the years. The 2014 WHO classification divides endometrial stromal sarcomas into low grade endometrial stromal sarcoma (LGESS) and high grade endometrial stromal sarcoma (HGESS), each demonstrating characteristic morphological, immunohistochemical and molecular events. Our knowledge of HGESS has significantly evolved since WHO 2014 classification with identification of distinct genetic alterations namely ZC3H7B- BCOR and YWHAE-NUTM2 gene fusions, associated with high grade histological features. We describe a case of endometrial stromal sarcoma showing high grade histological features but lacking either BCOR or YWHAE gene rearrangements and instead harbouring JAZF1 mutation typically associated with low grade endometrial stromal sarcomas. Method and Results: A 60 old female presented with postmenopausal bleeding. Imaging revealed a mass in the uterus suggestive of a uterine fibroid for which she underwent hysterectomy with bilateral salpingo-oophorectomy. Histological examination of the uterine mass revealed a uterine mesenchymal tumour diagnosed on histology as HGESS. However molecular studies revealed JAZF 1 mutation typically seen in LGESS. We describe detailed morphological, immunohistochemical and genetic alterations of this recently recognised entity. Conclusion: High grade transformation of low grade endometrial stromal sarcomas is exceedingly rare. High grade transformation in our case was identified at the time of initial diagnosis but can occur years after initial diagnosis. Awareness of this entity and recognition of high-grade features is important as despite JAZF1 abnormality, it shows high grade features which may indicate more aggressive behaviour